Reconstitution of the DTX3L–PARP9 complex reveals determinants for high-affinity heterodimerization and multimeric assembly. Issue 3 (11th February 2022) - Ashok, Yashwanth; Vela-Rodríguez, Carlos; Yang, Chunsong; Alanen, Heli I.; Liu, Fan; Paschal, Bryce M.; Lehtiö, Lari
Abstract : Ubiquitination and ADP-ribosylation are post-translational modifications that play major roles in pathways including the DNA damage response and viral infection. The enzymes responsible for these modifications are therefore potential targets for therapeutic intervention. DTX3L is an E3 Ubiquitin ligase that forms a heterodimer with PARP9. In addition to its ubiquitin ligase activity, DTX3L–PARP9 also acts as an ADP-ribosyl transferase for Gly 76 on the C-terminus of ubiquitin. NAD + -dependent ADP-ribosylation of ubiquitin by DTX3L–PARP9 prevents ubiquitin from conjugating to protein substrates. To gain insight into how DTX3L–PARP9 generates these post-translational modifications, we produced recombinant forms of DTX3L and PARP9 and studied their physical interactions. We show the DTX3L D3 domain (230–510) mediates the interaction with PARP9 with nanomolar affinity and an apparent 1 : 1 stoichiometry. We also show that DTX3L and PARP9 assemble into a higher molecular weight oligomer, and that this is mediated by the DTX3L N-terminal region (1–200). Lastly, we show that ADP-ribosylation of ubiquitin at Gly 76 is reversible in vitro by several Macrodomain-type hydrolases. Our study provides a framework to understand how DTX3L–PARP9 mediates ADP-ribosylation and ubiquitination through both intra- and inter-subunit interactions.